2022
DOI: 10.1002/med.21929
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial quality control proteases and their modulation for cancer therapy

Abstract: Mitochondria, the main provider of energy in eukaryotic cells, contains more than 1000 different proteins and is closely related to the development of cells. However, damaged proteins impair mitochondrial function, further contributing to several human diseases. Evidence shows mitochondrial proteases are critically important for protein maintenance. Most importantly, quality control enzymes exert a crucial role in the modulation of mitochondrial functions by degrading misfolded, aged, or superfluous proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 202 publications
0
17
0
Order By: Relevance
“…While the exact roles of ClpP in tumorigenesis are not clearly established, emerging evidence demonstrate that ClpP is overexpressed in multiple malignancies including breast cancers [ 261 , 262 , 263 ]. Recent analysis of TCGA database also confirmed that ClpP is overexpressed in breast and other cancers [ 264 ]. In addition, a high level of ClpP expression is associated with the disease stage, metastasis, poor prognosis and is proposed as a prognostic marker in breast cancers [ 261 , 265 , 266 ].…”
Section: Clppmentioning
confidence: 89%
See 1 more Smart Citation
“…While the exact roles of ClpP in tumorigenesis are not clearly established, emerging evidence demonstrate that ClpP is overexpressed in multiple malignancies including breast cancers [ 261 , 262 , 263 ]. Recent analysis of TCGA database also confirmed that ClpP is overexpressed in breast and other cancers [ 264 ]. In addition, a high level of ClpP expression is associated with the disease stage, metastasis, poor prognosis and is proposed as a prognostic marker in breast cancers [ 261 , 265 , 266 ].…”
Section: Clppmentioning
confidence: 89%
“…Since ClpP activators, but not ClpP inhibitors, show cytotoxicity in breast cancers, we will focus on ClpP activators in this review (for ClpP inhibitors, we refer readers to other excellent reviews [ 233 , 264 , 266 ]. There are three classes of ClpP agonists: acyldepsipeptide antibiotics (ADEPs), ONC201 and its analogs (imipridones), and TR compounds.…”
Section: Clppmentioning
confidence: 99%
“…Severe asthma is associated with energy metabolism dysfunction (Xu et al, 2022), and mitochondria play an important role in energy metabolism (Zhang et al, 2022). Bronchial epithelial cells play an essential role in asthma and mitochondrial dysfunction is implicated in asthmatic bronchial epithelial cells (AghapourRAPS et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria, as fundamental organelles for cellular and systemic metabolism, are critical in the fundamental biological processes including cellular differentiation, apoptosis, autophagy and hypoxic stress responses (AghapourRAPS et al, 2020;Larson-Casey et al, 2020;Zhang et al, 2022). Mitochondria dysfunction has been linked to a variety of disorders including cardiovascular disease, and cancer (Zhang et al, 2021;Vikramdeo et al, 2022;Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Precise delivery of anti-cancer drugs based on nano-drug delivery systems to subcellular targets, such as mitochondria, lysosomes, and nuclei, has already been considered as an excellent cancer treatment strategy ( Yang L. et al, 2022 ; Zhang J. et al, 2022 ; Wang et al, 2022 ). Mitochondria, the powerhouse of aerobic metabolism, exert an essential role in cellular physiological and pathological processes ( Song et al, 2019 ; Zhang S. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%